ENT 530 Social Media Portfolio: Zays Skincare / Syazwani Ayob - Ayob, Syazwani (2020)
Zays Skincare provide a line of Korean skincare product for customer who seek remedy in term of their skin condition by being their dropship. Our business offers are a line of Korean brands which each has their own uniqueness to help our customer in getting reliable product to achieve certain degree of healthy skin condition. In terms of our price range, we offer affordable and luxury skincare that each differs according to the brands which in the meantime helps customer to choose according to their price budget. In correlation, Zays Skincare are on mission of targeting customer who want to follow the trend of Korean beauty wave and also searching for beauty product that has been approved by dermatologist internationally. Since, the product is authentic our price offers may consider in the range of targeted audience with stable income. In addition, we also targeted both gender of female and male, as in this century of aesthetics people are more aware of the pivotal of having a skincare routine to obtain those ageless looks. Moreover, our business is operating through online platform for 24 hours which suits the situation of pandemic of COVID-19 that requires us to keep our social distance from any unwanted outbreaks. Basically, the customer is all around the Malaysia country regardless of every nook since they can easily access our Facebook Page with their electronic gadget such as smartphones, tablet and laptop. We deal with our potential buyer through Facebook and Whatapps and try to satisfy their question and needs as much as we can. This small business is basically operated and manages by Syazwani Binti Ayob at the moment. Our business used the online platform for marketing, business process and buying process and single handle by the owner. Most of the time the business activity includes hard sell, soft sell and teaser on promoting the Korean brand product to attained the customer reaction and feedback and also buying from than other dealers that competing in the same industry.